PENYULUHAN KESEHATAN MENUJU GENERASI SEHAT DI KELURAHAN LAMBUNG BUKIT KECAMATAN PAUH KOTA PADANG - Hindun Mila Hudzaifah; Yulizawati Yulizawati; Ulfa Farah Lisa; Laila Rahmi; Uliy Iffah; Feri Anita Wijayanti; Dina Taufia; Fannysia Halim; Shasi Genia Sanjaya; Monica Lailatul Murarah; Vivin Adella; Ovella April Rieza; Hadrah Alfina; Fira Rahmaditha; Trifia R ahmawati; Naomi Sondang (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Community midwifery is a midwifery service that emphasizes the psychosocial and cultural aspects of the community. This activity was carried out in RW 03 in the Lambung Bukit Village, Pauh District, Padang City through the Community Midwifery and Family Oriented Midwifery Education approach. Data were obtained which were the main problem that occurred in the Batu Busuk area community. inaccurate and waste disposal in ditches/rivers), skin diseases which are mostly suffered by toddlers and children and there is still a lack of variety in choosing the type of Family Planning (KB) method by couples of childbearing age (PUS) which is limited to the choice of Injectable KB methods and Pill. As a form of problem solving, interventions are carried out in the form of extension activities related to the problems found. The purpose of this activity is as a preventive and promotive effort in the form of midwifery services by involving community participation. The method used in prioritizing the problems found is using the weighting method, which is the process of assigning values ​​to selected problems to compare a criterion with other criteria by looking at the weight value. The conclusion of this activity is the implementation of counseling that can increase knowledge and change people's behavior so that they care more about clean and healthy living behavior (PHBS), know variations in choosing family planning methods and can ultimately improve the health status of the community as a whole.